BIOMASSA COMERCIAL DE Ilex paraguariensis St.-Hil. E SUA RELAÇÃO COM VARIÁVEIS AMBIENTAIS EM FLORESTA COM ARAUCÁRIA, PARANÁ - Signor, Pablo (2013)
This study aims to characterize the management practices for the production of erva-mate in an area of Floresta com Araucária, as well as analyze the floristic composition and phytosociology, adjust mathematical models for estimating commercial biomass of erva-mate (BC) and analyze soil variables and vegetation through of multivariate statistics. Management practices were described by the semi-structured interview. For vegetation were installed two permanent sampling units totaling 1.25 ha, divided into 125 subunits of 100 m?, which were identified, labeled and positioned with coordinates x, y all individuals with CAP ? 31.4 cm, also recorded; besides all the individuals of erva-mate composing the production system, for which was registered a circumference of 0.6 meters from the ground, the total height and early canopy, four canopy radius, the factor of canopy and biomass commercial determined with balance. Soil samples were collected at 0-20 cm depth for chemical and textural analyzes and the evaluation of the soil compression with digital penetrometer was made in 30 subunits distributed systematically on both units. For BC estimates, were tested the simple regression with one independent variable easily obtained and the procedure stepwise of variable selection. Management practices were characterized by mowing, canopy openness and conduction of natural regeneration, favoring mainly erva-mate and Araucaria; besides breeding. 22 species were found, with a predominance of Myrtaceae and Aquifoliaceae family. The Shannon index indicated consistently low diversity of the area, as well as Simpson demonstrated the dominance of Araucaria on other species and the Pielou recorded the low equity in the distribution of individuals among species. The equations with the best results of R? aj., Syx and graphical distribution of the residuals were obtained by Stepwise, which require the measurement of more independent variables, reducing the practicality of its use. The soils showed high acidity, low saturation of base and high of aluminum, and predominantly clayey texture and low compaction. Cluster analysis (CA) stratified with efficiency subunits based on the characteristics of the vegetation; the principal component analysis indicated the sand and clay as the most important in the formation of the main component of soil variation and that component alone could not explain variations in vegetation evidenced by CA.